Development of marketing models for attracting and retaining consumers in digital branding - Yahelska, Kateryna; Vasylyshyna, Liubov (Technology audit and production reserves, 2024)
The object of study is digital branding. The process of attracting and keeping consumers in digital branding is considered. The phenomenon of digital branding and the basic tools of its impact on consumers are investigated. The global trends in the development of media consumption at the present stage are substantiated. Transformational changes in the process of consumption, as a consequence, have been proven to be transition to the area. It is determined that in order to attract and maintain online consumers, brands should respond quickly and establish effective feedback. Accordingly, the important role of digital branding is indicated. As a basis for the development of a marketing model of consumer involvement and keeping in digital branding it is proposed to use the AIDA model. The marketing model is indicated that allows to monitor the actions of consumers, as well as to control communication processes. The stages of the AIDA model in digital branding are highlighted – visiting the site, moving the goods to the basket, registration and payment of order. AIDA strategic tools in digital branding are identified. It is necessary to use the conversion coefficient to determine the efficiency of each stage of the model. It is proposed to supplement the classic Aida model with two elements of Satisfaction (S) and Loyalty (L) by receiving AIDASL. An advanced model of impact on consumers in digital branding has been developed. This model coordinates the stages of the AIDASL model with the main stages of the purchase decision process. The practical importance of the developed model of consumer involvement and maintenance in digital branding will increase the attention, interest, desire and level of purchase. This, in turn, will create the preconditions for increasing conversion at each stage of consumer contact with an online store, increasing their satisfaction and loyalty.